2010
DOI: 10.1007/bf03256371
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and PTPN22 1858C/T Variant Analysis in Jordanian Arab Vitiligo Patients

Abstract: Although the PTPN22 1858C/T variant has been reported to play a role in increasing the risk of vitiligo in Caucasian patients, it does not appear to play a similar role in the Jordanian population, though a larger cohort of patients might be needed to confirm such a conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Similar to our results, in Gujarat Indian and Jordanian populations, the frequencies of the mutant (T) allele (0.79% and 2.14% in vitiligo patients and 2.14% and 2.9% in healthy controls, respectively) were lower than those of Caucasian populations (25). Furthermore, the homozygote (TT) genotype was absent in both generalized vitiligo patients and healthy controls in our study, as well as in the studies of Laddha et al10 and Alkhateeb et al11. These different findings on the frequencies of this polymorphism among Asian and Caucasian populations are attributed to ethnic differences.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar to our results, in Gujarat Indian and Jordanian populations, the frequencies of the mutant (T) allele (0.79% and 2.14% in vitiligo patients and 2.14% and 2.9% in healthy controls, respectively) were lower than those of Caucasian populations (25). Furthermore, the homozygote (TT) genotype was absent in both generalized vitiligo patients and healthy controls in our study, as well as in the studies of Laddha et al10 and Alkhateeb et al11. These different findings on the frequencies of this polymorphism among Asian and Caucasian populations are attributed to ethnic differences.…”
Section: Discussionsupporting
confidence: 66%
“…Laberge et al8 and LaBerge et al9 also identified an association between generalized vitiligo and the PTPN22 gene C>T single nucleotide polymorphism in both Romanian (65 Romanian patients with generalized vitiligo and 111 control subjects) and English-North American populations (126 families with multiple cases of generalized vitiligo) However, Laddha et al10 found no significant association between the PTPN22 1858 C>T polymorphism and generalized vitiligo in 126 Gujarat Indian patients with generalized vitiligo and 140 healthy controls. Similarly, Alkhateeb et al11 concluded that there is no significant correlation between the PTPN22 1858 C>T polymorphism and vitiligo in a Jordanian population consisting of 55 patients with generalized vitiligo and 85 healthy controls. Our results suggest that this single nucleotide polymorphism is not associated with generalized vitiligo in Turkish patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…49,[56][57][58][59][60][61][62][63][64][65][66][67] Americans of non-European descent showed a very low T allele frequency, as low as 1.1% in Mexico. 68 North Africa had a similar T allele frequency to Turkey and the Middle East, which ranged from 2 to 3.5%; [69][70][71][72][73][74][75] however, PTPN22 is not polymorphic in the black African population. 76 PTPN22 is also non-polymorphic or almost non-polymorphic in some Asian populations, including Japanese, Korean, Indian and some Chinese populations.…”
mentioning
confidence: 89%
“…A meta-analysis utilizing data from different ethnicities shows an association of PTPN22 C1858T with vitiligo in European but not in Asian population [28]. In contrast, no significant association of PTPN22 C1858T polymorphism with susceptibility to generalized vitiligo was found in Indian Gujarat population, Jordanian, Egyptian female, and Turkish population [27,[32][33][34]. Available literature shows that the variant of PTPN22 C1858T is responsible for increased risk of vitiligo in Caucasian patients; however, among non-Caucasians/Asians, inconsistency exits, and even the two populations of same country differ in association of PTPN22 C1858T with vitiligo indicating the role of ethnicity.…”
Section: Vitiligomentioning
confidence: 99%